2018
DOI: 10.4049/jimmunol.1700562
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Recruit CCR2+ Monocytes To Suppress Allergic Airway Inflammation

Abstract: Mesenchymal stem cells (MSC) exert immune modulatory properties and previous studies demonstrated suppressive effects of MSC treatment in animal models of allergic airway inflammation. However, the underlying mechanisms have not been fully elucidated. We studied the role of MSC in immune activation and subsequent recruitment of monocytes in suppressing airway hyperresponsiveness and airway inflammation using a mouse model of allergic airway inflammation. MSC administration prior to or after allergen challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…The airway epithelium is considered an essential controller of the inflammatory, immune, and regenerative responses to the allergens, viruses, and environmental pollutants that contribute to asthma pathogenesis ( Lambrecht and Hammad, 2012 ). Increasing evidence shows that MSC transplantation can functionally ameliorate lung injury ( de Castro et al., 2017 , Takeda et al., 2018 , Tilokee et al., 2016 ). Our previous studies demonstrated that intravenous injection of iPSC-MSCs inhibited allergic airway inflammation and permitted a rebalancing of the immune response in a mouse model ( Sun et al., 2012 , Wang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The airway epithelium is considered an essential controller of the inflammatory, immune, and regenerative responses to the allergens, viruses, and environmental pollutants that contribute to asthma pathogenesis ( Lambrecht and Hammad, 2012 ). Increasing evidence shows that MSC transplantation can functionally ameliorate lung injury ( de Castro et al., 2017 , Takeda et al., 2018 , Tilokee et al., 2016 ). Our previous studies demonstrated that intravenous injection of iPSC-MSCs inhibited allergic airway inflammation and permitted a rebalancing of the immune response in a mouse model ( Sun et al., 2012 , Wang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that mesenchymal stem cell (MSC)-based therapy shows promising results for allergic airway inflammation ( Cruz et al., 2015 , Dai et al., 2017 , Takeda et al., 2018 ). We have demonstrated that MSCs derived from induced pluripotent stem cells (iPSC-MSCs) not only effectively inhibit allergic airway inflammation and alleviate asthma in a mouse model but also modulate T cell phenotypes in allergic rhinitis patients ( Fu et al., 2012 , Sun et al., 2012 ), indicating that iPSC-MSC-based therapy could be relevant to the treatment of allergic airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…MSC-exosomes reportedly modulate MΦ phenotype, suppressing the proinflammatory M1-like state and shifting the M2-like MΦ to favor an anti-inflammatory, pro-regulatory phenotype both in vitro and in vivo [197,198]. However, exosomes extracted from cells cultured in cardiometabolic disease [199][200][201][202][203][204][205] mimicking conditions or from biological fluids of diabetic patients, produce pathogenic microangiopathic effects [201,202]. Taken together, extreme caution should be exercised when considering the use of 'naïve' patient-derived exosomes for therapeutic intervention.…”
Section: Novel Therapeutic Approaches In Gestational Diabetes Mellitusmentioning
confidence: 99%
“…In contrast, several reports indicate that allogenic "healthy" MSCs are an excellent source of bioactive exosomes [203], endowed with protective, antifibrotic and proangiogenic properties [204]. Additionally, MSCs reportedly recruit CCR2+ monocytes (Mo), which were shown to contribute to the regenerative properties induced by stem cell injection into the rodent heart [192,205]. Although great success has already been achieved using cell therapy with mesenchymal stem cell (MSC), many aspects related to their effectiveness and side effects need to be deciphered, including their potential carcinogenicity [79,206,207] as well as their migratory ability (to different sites) and the resulting engraftment potential [208][209][210].…”
Section: Novel Therapeutic Approaches In Gestational Diabetes Mellitusmentioning
confidence: 99%
“…81,82 In an airway inflammation model, MSCs were able to recruit CCR2þ monocytes into the lungs due to stimulation by IFN-γ which increased the expression of CCL2. 41 Macrophages: Macrophages are an integral part of the innate immune system where they are responsible for developmental and metabolic activities and most importantly immunological function to maintain a state of homeostasis. 83 Their activity largely depends on the microenvironment they are exposed to with the initial inflammatory phase of infection and injury inducing an inflammatory M1 phenotype and the later resolution phase mainly involving an anti-inflammatory M2 phenotype.…”
Section: Seminars In Respiratory and Critical Care Medicinementioning
confidence: 99%